Uji Fitokimia Ekstrak Kulit Buah Salak (Salacca zalacca) dan Pengaruh Ekstrak terhadap Pertumbuhan Bakteri Streptococcus mutans dan Jamur Candida albicans - Emma Susilowati Shabir; Agung Rahmadani; Lisna Meylina; Hadi Kuncoro (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2018)
Snakefruit (Salacca zalacca) is one of Indonesian native plant that the pericarp of snakefruit can be used because it has activity as an antimicrobial. This study aims to identify the metabolite content of snakefruit pericarp and to investigate the potential of snakefruit pericarp extracts in inhibiting the growth of Streptococcus mutans and Candida albicans. Snakefruit pericarp was extracted by reflux method using ethanol 96%, and an extract was tested by phytochemical qualitatively and antimicrobial activity of extract was carried out using the well method, by using concentrations are 5, 10, 15, and 20%. The results showed that the extracts contains secondary metabolites i.e. alkaloids, flavonoids, saponins and tannins. Extract of snakefruit pericarp can inhibit the growth of Streptococcus mutans and Candida albicans at 5% concentration and the inhibiting activity increased together with higher concentrations of extract.